The role of achievement motivation in the process of socialisation of gifted adolescent - G. Gulko,; A. Lisova, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article defines the current trends of interpretation of achievement motivation and socialization from a position of national and foreign scientists. We pose the problem of the presence, causes and consequences of the influence of structural components of p socialization process on the leading motives for learning. Presented the results of the empirical research of socialization level and structure of academic motivation for adolescents.
Keywords: achievement motivation; socialization; adolescence; educational space; structure of the academic motivation; socialization structure; giftedness